Crystal structures and mechanical properties of osmium diboride at high pressure - Yi X. Wang (Nature Portfolio, 2021)
Abstract We have investigated the crystal structures and mechanical properties of osmium diboride (OsB2) based on the density functional theory. The structures of OsB2 from 0 to 400 GPa were predicted using the particle swarm optimization algorithm structure prediction technique. The orthorhombic Pmmn structure of OsB2 (oP6-OsB2) was found to be the most stable phase under zero pressure and it will transfer to the hexagonal P63/mmc structure (hP6-OsB2) around 12.4 GPa. Meanwhile, we have discovered a new stable orthorhombic Immm structure (oI12-OsB2) above 379.6 GPa. After that, a thorough and comprehensive investigation on mechanical properties of different OsB2 phases is performed in this work. Further studies showed that the hardness of oP6-OsB2 and hP6-OsB2 at zero pressure is 15.6 and 20.1 GPa, while that for oI12-OsB2 under 400 GPa is 15.4 GPa, indicating that these three phases should be potentially hard materials rather than superhard materials. Finally, the pressure–temperature phase diagram of OsB2 is constructed for the first time by using the quasi-harmonic approximation method. Our results showed that the transition pressures of oP6-OsB2 → hP6-OsB2 and hP6-OsB2 → oI12-OsB2 all decreases appreciably with the increase of temperature.